2012
DOI: 10.1002/jor.22287
|View full text |Cite
|
Sign up to set email alerts
|

Local insulin therapy affects fracture healing in a rat model

Abstract: A significant number of lower extremity fractures result in mal-union necessitating effective treatments to restore ambulation. Prior research in diabetic animal fracture models demonstrated improved healing following local insulin application to the fracture site and indicated that local insulin therapy can aid bone regeneration, at least within an insulin-dependent diabetic animal model. This study tested whether local insulin therapy could accelerate femur fracture repair in normal, non-diabetic rats. High … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
39
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 28 publications
4
39
1
1
Order By: Relevance
“…Other data suggests that insulin is directly anabolic for bone formation . BB Wistar rats develop spontaneous insulin‐dependent diabetes.…”
Section: Disease: Additional Inhibitory Factorsmentioning
confidence: 99%
“…Other data suggests that insulin is directly anabolic for bone formation . BB Wistar rats develop spontaneous insulin‐dependent diabetes.…”
Section: Disease: Additional Inhibitory Factorsmentioning
confidence: 99%
“…The use of insulin or insulin‐mimetic agents can accelerate fracture healing in experimental animal models . The evaluation of scaffolds for appropriate drug delivery of these therapeutic modalities may combat the annual 5–10% of fractures that result in non‐union .…”
mentioning
confidence: 99%
“…We previously showed that local insulin delivery to bone fracture sites promotes osteogenesis during the first 4–7 days of healing, but the effectiveness is limited when insulin is directly injected into the intramedullary (IM) canal . The use of palmitic acid and calcium sulfate (CaSO 4 ) as insulin carriers prolonged local bioavailability of insulin at bone fracture sites and improved healing as compared to insulin treatment without a carrier based upon biomechanical and histological healing outcomes . The use of these carriers also improved the therapeutic safety of insulin, evidenced by blood glucose levels within 12–24 h of insulin administration .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have found systemic insulin treatment increased cell proliferation, soft callus formation/chondrogenesis, biomechanical properties, and callus bone content in diabetes mellitus rats [12]. Furthermore, local administration of insulin has been found to improve healing and bone regeneration in animal models [13,14]. However, insulin is difficult to deliver locally due to its high molecular weight (MW) (51 amino acids and 5,808 Da MW) and stability; insulin goes through hydrolysis/ degradation or intermolecular transformation during storage and use [15].…”
Section: Introductionmentioning
confidence: 96%